Does research activity decline with age? - Zoega, Gylfi (Veftímaritið Stjórnmál og stjórnsýsla, 2017)
Several economic models predict that effort may decline as retirement approaches. These models are reviewed and data from the University of Iceland used to measure how research productivity of members of staff depends on age. We find support for the hypothesis that men are at a greater risk of becoming inactive when they approach retirement. Moreover, men tend to be more research active than women in their thirties and forties but lose their edge in their fifties and sixties. Finally, we detect a cohort effect such that later cohorts are more productive than earlier ones.